Seismogenic structures along the deformation front from onshore to offshore SW Taiwan - Wen-Nan Wu; Jing-Yi Lin; Wen-Bin Doo; Chung-Liang Lo; Shu-Kun Hsu (Geoscience Letters, 2024)
Abstract Accurately imaging seismogenic structures is crucial for seismic hazard assessment. This is especially important around the deformation front (DF) region off SW Taiwan, where seismic potential is high but the fault structure and seismic activity are still poorly understood. Here, we present a comprehensive delineation of seismogenic structures along the onshore and offshore DF of SW Taiwan, utilizing hypocenter relocations and first-motion focal mechanism solutions from January 1991 to March 2019. Five distinctive seismogenic structures are delineated. Particularly, the energetic seismic activity initialled after the 2017 Mw5.3 Tainan earthquake and migrated northeastward along the western side of the DF. The offshore trace of the DF could serve as a boundary delimiting the seismic activity driven by the flexural stress of the subducted Eurasia Plate to the west of the DF. This observation could constrain the magnitude estimation of future earthquakes offshore SW Taiwan. Meanwhile, the areas with higher seismic moment release are located near the DF rather than known faults, indicating that the DF may dominate the seismic moment release. However, further study is warranted into the intricate relationship among seismic strain variation, the structure of DF, and seismic activity to further understand the seismic potential. Our first-motion focal mechanism solutions show that several earthquakes in SW Taiwan were characterized by P-axis orientations parallel to the strike of the Taiwan orogeny. Those events are preferably explained by the lateral compression induced by the ongoing collision between the Eurasia and Philippine Sea plates.